Pelatihan Pemanfaatan Media Geogebra Berbasis Teknologi dalam Pembelajaran Matematika di SMA Negeri 1 Wundulako - Ramlan, Andi Mariani; Hali, Fitriyani; Jumriah, Jumriah (Vokasi Universitas Halu Oleo, 2019)
The problems of this service include: 1) the lack of skills of mathematics teachers in the use of geogebra media; 2) the lack of knowledge of mathematics teachers to develop teaching aids based on technology. The solution proposed by PKMS is to provide training on the use of geogebres in mathematics learning, which aims to: (1) improve the skills of mathematics teachers in the use of geogebres in learning; 2) increase teachers' knowledge to develop technology-based teaching materials. The problem-solving framework for this training activity has several stages, namely: 1) preparation; 2) inventory of participants in the training; 3) preparation of training materials; 4) presentation of training materials; (5) to provide an opportunity for mathematics teachers who have been selected to carry out the design of technology-based teaching materials, accompanied by a team of experts; 6) report preparation. The results of this activity show that the trainees were able to use geogebra media for mathematics learning.